2009
DOI: 10.1016/j.jacc.2008.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Venous Congestion for Worsening of Renal Function in Advanced Decompensated Heart Failure

Abstract: Background Reduced cardiac output is traditionally believed to be the main determinant of worsening renal function (WRF) in advanced decompensated heart failure (ADHF). Objective To determine if venous congestion, rather than impairment of cardiac output, is primarily associated with the development of WRF in ADHF. Methods A total of 145 consecutive patients admitted with ADHF treated with intensive medical therapy guided by pulmonary artery catheter were studied. WRF was defined as an increase of serum cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
644
3
25

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,381 publications
(693 citation statements)
references
References 34 publications
(24 reference statements)
21
644
3
25
Order By: Relevance
“…Venous congestion, not diuretic use, was the strongest determinant for the development of WRF. 23 Discussion HF treatment has changed tremendously over the last 2 decades, most notably with medications that inhibit RAAS and SNS. 24 Loop diuretics have been utilized prior to our full understanding of the roles of RAAS and SNS in HF pathophysiology.…”
Section: Clinical Studies In Heart Failurementioning
confidence: 99%
“…Venous congestion, not diuretic use, was the strongest determinant for the development of WRF. 23 Discussion HF treatment has changed tremendously over the last 2 decades, most notably with medications that inhibit RAAS and SNS. 24 Loop diuretics have been utilized prior to our full understanding of the roles of RAAS and SNS in HF pathophysiology.…”
Section: Clinical Studies In Heart Failurementioning
confidence: 99%
“…Traditionally, AKI has been attributed to hypoperfusion of the kidney because of progressive impairment of the cardiac output 15. However, attention has shifted from this cardiac output (‘forward failure’) to venous congestion (‘backward failure’) as the most important haemodynamic determinant 1. Current evidences did not support low cardiac output as the main determinant of renal dysfunction in patients with AHF 1, 16.…”
Section: Discussionmentioning
confidence: 99%
“…However, attention has shifted from this cardiac output (‘forward failure’) to venous congestion (‘backward failure’) as the most important haemodynamic determinant 1. Current evidences did not support low cardiac output as the main determinant of renal dysfunction in patients with AHF 1, 16. The development of ‘congestive kidney failure’ induced by the increased renal venous pressure arising from venous congestion (increased renal afterload) and increased renal interstitial pressure (intrinsic renal compromise) might be important mechanisms underlying the development of renal dysfunction in AHF patients 1…”
Section: Discussionmentioning
confidence: 99%
“…However, we have shown that the optimization of pharmacological treatment during the first year of follow‐up was associated with a relative risk reduction of HF/death, which suggests a complementary effect of CRT and up‐titration of pharmacological therapy. The reason for this improvement might be that CRT provides acute hemodynamic improvement,19, 20, 21, 22 with an increase in cardiac output and a reduction in pulmonary capillary wedge and improvement in the mechanical activation sequence. Cardiac resynchronization therapy also supports systemic blood pressure and heart rate, enabling an increase in the doses of drugs without the associated risk of lethal bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%